Theoretical Study of Light-Induced Crosslinking Reaction Between Pyrimidine DNA Bases and Aromatic Amino Acids - Bende, Attila; Farcaş, Alex-Adrian; Toşa, Valer (Frontiers in Bioengineering and Biotechnology, 2022)
Low-lying electronic excited states and their relaxation pathways as well as energetics of the crosslinking reaction between uracil as model system for pyrimidine-type building blocks of DNA and RNA and benzene as model system for aromatic groups of tyrosine (Tyr) and phenylalanine (Phe) amino acids have been studied in the framework of density functional theory. The equilibrium geometries of the ground and electronic excited states as well as the crossing points between the potential energy surfaces of the uracil-benzene complex were computed. Based on these results, different relaxation pathways of the electronic excited states which lead either back to the initial geometry configuration or the dimerization between the six-membered rings of the uracil-benzene complex have been identified and the energetic conditions for their occurrence are discussed. It can be concluded that the DNA-protein crosslinking reaction can be induced by the external electromagnetic field via the dimerization reaction between the six-membered rings of the uracil-benzene pair at the electronic excited state level of the complex. In the case of uracil-phenol complex the configuration of the cyclic adduct (dimerized) conformation is less likely to be formed.